STEM Education in New Zealand at the Senior Secondary Level: Cross-Curricula Course Design and Assessment for NCEA - Granshaw, Bruce; Hall, Cedric (Australasian Journal of Technology Education, 2017)
This paper considers the design and assessment of Integrative-STEM courses at senior secondary level in New Zealand. Integrative-STEM education places emphasis on students drawing together knowledge from science, technology, engineering and mathematics, in order to solve design problems. The paper identifies important elements of an integrative-STEM course and whether the current range of NCEA achievement standards provides a suitable fit for assessing students’ STEM learning. The conclusion reached is that a partial fit exists at Levels 2 and 3 of NCEA but a stronger fit exists at Level 1. For comparative purposes, the paper also considers how well the design of NCEA social science achievement standards harmonise with cross-curricula course design. The interpretation is suggested that the subject-by-subject development of NCEA standards provides significant limitations on the validity of assessment of cross-curricula learning. Some of the important learning engendered by cross-curricula design lies outside the assessment covered by NCEA standards.Â 